(untitled) (Texas Journal of Medical Science, 2022)
Infertility is one of the most pressing problems of our time. Because every married family wants to have children, and it’s not just a matter of desire. The saddest part of this is that it can lead to divorce. This article is about the most common type of female infertility, the nay type.